An investigation into the feasibility of bioleaching copper sulphide ore of Nchanga mine, Chingola, Zambia - Manchisi, James (Department of Chemical Engineering, 2023)
Bioleaching is now well established for extraction of copper from its low-grade, mixed oxide/sulphide ores in bioheap operations (Watling, 2006). It is claimed bioleaching may be a cheaper alternative to other traditional metal extraction techniques such as smelting and therefore more suitable to treat marginal or low-grade ores where high-grade mineral reserves have been depleted. But the degree of microbial oxidation for different copper sulphides varies significantly partly because of different types and level of impurity minerals associated with copper sulphides from different sources. Several authors have reported different mineral leaching kinetics data on account of variability of mineralogical composition and different solution conditions and leaching systems being employed. This has indicated that further work was necessary to determine the kinetics of copper extraction, extent of mineral dissolution and effects of some leaching variables on copper dissolution for an ore from Nchanga mine under various solution conditions.